Effect of exposure to radiation caused by an atomic bomb on endothelial function in atomic bomb survivors - Kishimoto, Shinji; Oda, Nozomu; Maruhashi, Tatsuya; Tanigawa, Shunsuke; Mizobuchi, Aya; Yusoff, Farina Mohamad; Fujita, Asuka; Uchiki, Toshio; Kajikawa, Masato; Yoshimura, Kenichi; Yamaji, Takayuki; Harada, Takahiro; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: The purpose of this study was to evaluate the effects of exposure to radiation caused by an atomic bomb in atomic bomb survivors on vascular function and vascular structure and to evaluate the relationships of radiation dose from the atomic bomb with vascular function and vascular structure in atomic bomb survivors. Methods: Flow-mediated vasodilation (FMD) and nitroglycerine-induced vasodilation (NID) as indices of vascular function, brachial-ankle pulse wave velocity (baPWV) as an index of vascular function and vascular structure, and brachial artery intima-media thickness (IMT) as an index of vascular structure were measured in 131 atomic bomb survivors and 1153 control subjects who were not exposed to the atomic bomb. Ten of the 131 atomic bomb survivors with estimated radiation dose in a cohort study of Atomic Bomb Survivors in Hiroshima were enrolled in the study to evaluate the relationships of radiation dose from the atomic bomb with vascular function and vascular structure. Results: There was no significant difference in FMD, NID, baPWV or brachial artery IMT between control subjects and atomic bomb survivors. After adjustment of confounding factors, there was still no significant difference in FMD, NID, baPWV or brachial artery IMT between control subjects and atomic bomb survivors. Radiation dose from the atomic bomb was negatively correlated with FMD (ρ=-0.73, P=0.02), whereas radiation dose was not correlated with NID, baPWV or brachial artery IMT. Conclusions: There were no significant differences in vascular function and vascular structure between control subjects and atomic bomb survivors. Radiation dose from the atomic bomb might be negatively correlated with endothelial function.